Adult presence augments juvenile collective foraging in social spiders. (November 2015) - Modlmeier, Andreas P.; Laskowski, Kate L.; Brittingham, Hayley A.; Coleman, Anna; Knutson, Karen A.; Kuo, Candice; McGuirk, Matthew; Zhao, Katherine; Keiser, Carl N.; Pruitt, Jonathan N.
Abstract : The presence of a few highly influential individuals, so called 'keystone individuals', is thought to influence group dynamics and success in a diverse variety of animal societies. Although older, experienced individuals often occupy keystone roles such as leader or dominant individual, few studies have performed manipulations to study their impact. Here, we investigate how juvenile collective foraging behaviour is influenced by adult presence in the social spider Stegodyphus dumicola . Our manipulation of age demography revealed that the presence of a few mature females drastically increased a groups' foraging aggressiveness, demonstrating that adults indeed act as keystone individuals in juvenile spider groups. Interestingly, the magnitude of their positive impact on collective foraging was mediated by group size: adult presence shortened latency to attack prey more strongly in large groups than in small groups. Conversely, adult presence increased the number of attackers only in small groups. Surprisingly, intergroup variation in collective foraging, which is known to be consistent in mature social spiders, was not repeatable in juvenile groups. Thus, juvenile groups seem to behave more erratically or need more time to develop collective personalities. Together, our results suggest that adult presence can have profound, catalytic effects on juvenile collective foraging behaviour, and that these effects are modulated by group size. Highlights: Adult presence enhances juvenile collective foraging in social spider colonies. Adults do not participate, but somehow increase juvenile foraging aggressiveness. Group size mediates the magnitude of the adult's catalytic effect. Adults always improve attack speed, but the effect is stronger in large groups. Adult presence augments juvenile hunting group size only in small groups.